A new approach to neurocontrol based on Fourier analysis and nonuniform multi-dimensional sampling - Dzieliński, Andrzej; Żbikowski, Rafał (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a new approach to neurocontrol of deterministic, discrete-time non-linear (NARMA) dynamic systems, given only input-output data of finite length. The demanding setting of scarce knowledge about the plant is motivated by practice of data acquisition and the complexity of discretised dynamics. The essence of the method is a novel modelling technique based on nonuniform multi-dimensional (N-D) sampling and Fourier Analysis.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka